The anti-inflammatory and tolerogenic potential of small spleen peptides - Wixler, Viktor; Zaytsev, Igor Z.; Boergeling, Yvonne; Ludwig, Stephan (Frontiers in Immunology, 2024)
Maintaining peripheral immune tolerance and preventing harmful autoimmune reactions is a fundamental task of the immune system. However, these essential functions are significantly compromised during autoimmune disorders, creating a major challenge in treating these conditions.In this context, we provide an overview of research on small spleen polypeptides (SSPs) that naturally regulate peripheral immune tolerance. Alongside outlining the observed effects of SSPs, we summarize here the findings on the cellular and molecular mechanisms that underlie their regulatory impact. Specifically, SSPs have demonstrated remarkable effectiveness in halting the progression of developing or established autoimmune disorders like psoriasis or arthritis in animal models. They primarily target dendritic cells (DCs), swiftly prompting the production of extracellular ATP, which is then degraded and sensed by adenosine receptors. This process triggers the mTOR signaling cascade, similar to powerful immune triggers, but instead of a rapid and intense reaction, it leads to a moderate yet significant activation of the mTOR signaling cascade. This induces a tolerogenic state in dendritic cells, ultimately leading to the generation of Foxp3 + immunosuppressor Treg cells. In addition, SSPs may indirectly attenuate the autoimmune response by reducing extracellular ATP synthesis in non-immune cells, such as endothelial cells, when exposed to elevated levels of proinflammatory cytokines. SSPs thus have the potential to contribute to the restoration of peripheral immune tolerance and may offer valuable therapeutic benefits in treating autoimmune diseases.